2011 International Conference on Parallel Processing 2011
DOI: 10.1109/icpp.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Eager Meets Lazy: The Impact of Write-Buffering on Hardware Transactional Memory

Abstract: Abstract-Hardware transactional memory (HTM) systems have been studied extensively along the dimensions of speculative versioning and contention management policies. The relative performance of several designs policies has been discussed at length in prior work within the framework of scalable chipmultiprocessing systems. Yet, the impact of simple structural optimizations like write-buffering has not been investigated and performance deviations due to the presence or absence of these optimizations remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In this paper, we extend the exploration of transactional store management presented in our previous work [16]. However, our primary focus now is on eager HTM designs.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this paper, we extend the exploration of transactional store management presented in our previous work [16]. However, our primary focus now is on eager HTM designs.…”
Section: Introductionmentioning
confidence: 93%
“…As opposed to EE, lazy systems easily discard speculative state in a few cycles. However, the difference in execution time with LL_ideal_bufferL1 is less notable, as the number of contamination misses is large [16].…”
Section: Comparison Against Idealized Ll Systemsmentioning
confidence: 98%
“…While store-buffers do provide this benefit to a certain extent, having the cache act as a precoherence buffer would potentially provide much larger performance benefits. Negi et al [2011] have studied the impact of such buffering on eager designs and found substantial performance gains could be achieved.…”
Section: Using the Cache Designs To Build An Htm Systemmentioning
confidence: 98%
“…Prior work [17] has found that containing transactional stores in dedicated hardware buffers can mitigate overheads associated in reading back lines invalidated on an abort. However, our prefetching technique provides improvements in performance for fresh transaction invocations as well.…”
Section: Motivationmentioning
confidence: 99%
“…Yet others have attempted to incorporate the best of both eager and lazy policies in one design -at the granularity of application phases [19], at the granularity of transactions [15] , and at the granularity of cache lines [24]. There exist studies that have attempted to insulate the coherent cache hierarchy from adverse effects of repeated aborts [17]. These varied attempts at reducing overheads involved in shared data accesses by cooperating threads have motivated the design effort in this work.…”
Section: Related Workmentioning
confidence: 99%